EMPOWERING STRAWBERRY CULTIVATION: HARNESSING THE POTENTIAL OF IOT-BASED TECHNOLOGY IN SMART FARMING - Kartika Sari; Rahmi Hidayati; Irma Nirmala; Uray Ristian (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Agro-tourism is a form of tourism that uses agricultural land or related facilities to attract tourists. One popular agro-tourism site in Rasau Jaya Tiga is the Inspirasi Strawberry Park. Until now, the manual watering has been a common practice for strawberry plants. The Problem in watering strawberry plants manually is that inconsistent watering schedules often lead to overwatering or underwatering, affecting plant health and yield. Therefore, there is a necessity for an automated system to ensure precise and consistent watering, optimizing plant growth, water efficiency, and overall crop quality. By developing an Internet of Things (IoT) integrated irrigation system for strawberry plants, strawberry plants can be watered automatically and controlled through the Internet or mobile devices, using soil moisture sensors, air temperature, and intelligent decision-making. The results of this study indicate that the automatic watering system is able to accurately collect real-time data on temperature, humidity, time, and date of data collection. Additionally, the automatic scheduling system for watering plants and lighting system can operate as intended. With the implementation of an IoT-based automatic irrigation system for strawberry cultivation, labor costs are reduced, and crop yields are increased, contributing to enhanced agricultural productivity and economic sustainability.